Pollen, grain size, loss-on-ignition, elemental and mineralogical composition, magnetic susceptibility and radiocarbon measurements in Hashilan Wetland sediment core - Safaierad, Reza; Zolitschka, Bernd; Djamali, Morteza; Dupont, Lydie M; Vogt, Christoph; Matthews, Roger (PANGAEA, 2023)
The proxy data reported here are measured from a sediment core collected from the Hashilan Wetland (34° 34' 55 N, 46° 53' 13 E, 1310 m a.s.l.) in the Zagros Mountains of western Iran. The core is 315 cm long (from 85 to 400 cm under the wetland surface) and was collected using a peat corer on November 10th, 2016.
Keywords: Atmospheric dust; Grain Size; Holocene climate; loss on ignition; Magnetic susceptibility; Pollen; Vegetation dynamics; XRD; XRF